Influence of Green Practices and Environmental Awareness on Intention to Visit: The Case of Shopping Malls in Makati City, Philippines - Jenalyn Q. Pones; Nicole Versoza; Allyssa Kristel Estapia; Jayvie O. Guballo (Journal of Management Studies and Development, 2026)
This study explores the influence of green practices, environmental consciousness on consumers’ willingness to visit shopping malls, focusing on Ayala Malls in Makati City. As environmental sustainability gains traction, malls increasingly adopt eco-friendly initiatives to attract and retain environmentally aware shoppers. This research specifically investigates how sustainability efforts such as waste management systems, energy-efficient infrastructure, and green open spaces influence consumer attitudes and visit intentions. The objective is to determine how environmental awareness and green practices contribute to consumers' shopping intentions, and which initiatives most effectively foster positive perceptions and behaviors. A quantitative research design was used, gathering data from 385 via a structured questionnaire. Regression analysis was applied to assess the impact of green practices and environmental consciousness on mall visitation intent. Findings reveal a strong consumer preference for environmentally sustainable shopping environments. Respondents highlighted visible recycling measures, bicycle parking, and active sustainability campaigns as key factors shaping positive mall experiences. These green features were significantly influenced by the increased likelihood of mall visits. The study underscores the importance of enhancing green initiatives within malls. Recommendations include simplifying waste management systems, introducing sustainable consumption incentives, and embedding sustainability in corporate social responsibility (CSR) efforts. These strategies not only boost consumer engagement but also support long-term business viability. Future researchers may consider examining the changing consumer behavior trends and asses the long-term business value of green practice.